Spatio-temporal evolution and driving mechanism of ecosystem services in typical hilly and gully areas of the loess Plateau: A case study in Yan’an Region, Shaanxi Province - Qiaoyang Yang; Hui Qian; Yanyan Gao; Yicheng Duan; Zhiming Cao; Panpan Tian; Kang Li; Shuhan Yang; Weijie Zhao; Qi Long (Ecological Indicators)
Accurately understanding the interactions among ecosystem services (ESs) and analyzing their complex driving mechanisms is crucial for enhancing ESs on the Loess Plateau. Yan’an is a typical loess hilly and gully area facing serious population-land-food conflicts. It is necessary to systematically expound the relationship between ecological environment and grain production (GP). By using GeoDetector and Geographic Weighted Regression (GWR) models, this study investigated the spatio-temporal evolution, trade-offs/synergies and driving forces of four ESs interactions: water yield (WY), soil conservation (SC), carbon sequestration (CS), and GP. The results revealed that between 1990 and 2020, (1) The increases in WY, SC, CS, and GP indicated a significant enhancement of ESs in Yan’an; (2) The spatial distributions of WY, CS, and GP showed similar patterns, generally increasing from north to south, whereas SC was relatively scattered; (3) The synergistic effects among ES pairs in Yan’an outweighed trade-offs. The WY-GP pair exhibited the strongest synergy, whereas the SC-CS pair showed the weakest; (4) Natural factors such as precipitation and temperature indirectly affect ESs by directly influencing surface hydrological processes; (5) Policies primarily affect ESs by driving changes in land use: The proportion of forest, grassland, and building land influence precipitation, surface runoff generation, and sediment transport, thereby affecting WY, SC, and CS, whereas GP is mainly driven by urbanization. Based on four ESs, this study developed an ecosystem services comprehensive index (ESCI), which increased from 0.56 to 0.60. Additionally, areas with good-quality ESs exhibited a consistent expansion from south to north spatially. These findings offer a scientific and practical reference for evaluating ecosystem quality on the Loess Plateau and for guiding land resource management influenced by the interplay of natural-human-policy factors.